Dakwah Lingkungan Sebagai Alternatif Dalam Menyelesaikan Masalah Perubahan Iklim - Abdurrahman Hilabi (STAI Publisistik Thawalib Jakarta, 2023)
The purpose of this research is to explain the implementation of preaching about the environment to overcome the problem of climate change in society. Qualitative research methods with a library study approach. Data collection techniques with documentation studies and data processing with reduction and presentation of data. The results showed: environmental preaching is preaching that is directed at improving and protecting the surrounding environment in the face of global climate change. The purpose of this da'wah is to make people aware of the importance of protecting the surrounding environment which is carried out by providing education to the community, environmental campaigns, developing environmentally friendly products, counseling, and training on the utilization of surrounding environmental resources. With this environmental preaching, it is hoped that the community will become more aware and be able to protect the environment so that it becomes more friendly and beneficial to the surrounding community.